Vacancy at the edges of the precarious city - Ferreri, M; Vasudevan, A (Elsevier, 2019)
In this paper, we examine the relationship between precarity, property and urban vacancy. Our main aim is to develop a conceptual framework that connects recent geographical scholarship on precarity to the production of vacant urban landscapes. The paper extends recent geographical scholarship on urban vacancy as a key site of antagonism for post-crisis forms of urbanisation. In so doing, it highlights the role of urban vacancy as a key feature in the making of the precarious city. Particular attention is paid to the rise of Property Guardianship and its relationship to the production and management of vacant urban land and property in the case of the ongoing financialisation of housing in London. Vacancy, in this context, is best understood as a spatial process that produces a varied geography of insecurity and disposability. This is, moreover, a geography that must be positioned within wider and longer trajectories in the urbanisation of injustice. The paper therefore combines a contemporary analysis of guardians living 'on the city's edge' with a historical look back at the 1970s and the little-known practice of 'short-life co-operative housing'. Taking a longitudinal view on the management of vacant buildings through temporary living arrangements across the last forty years enables us to examine old and new geographies of housing precarity and their relationship to the logics of large scale urban transformation.